Nurturing the Self: How Interpersonal Relationships Foster Individual Development - Adelia Fristiana Putri; Mayang Ayu Angelita Sari; Rizky Akbar Dwi Alvaridzi (International Conference on Psychology and Education (ICPE), 2023)
The purpose of this study is to find out how interpersonal relationships can foster individual self-development. The research method uses a qualitative approach with a literature review through research searches with the selected keywords, namely "Interpersonal", "Interpersonal Relationships", and "Individual Development". From the research that has been done, it can be concluded that interpersonal interactions have a positive impact on personal development. Studies indicate that having positive interpersonal relationships can enhance self-confidence, communication skills, and understanding of others' emotions. Additionally, good interpersonal relationships help build social support networks, improve the ability to express oneself, avoid conflicts, and promote cooperation with others. Therefore, it is important to support and strengthen positive interpersonal relationships to enhance overall individual development.